Fatigue Increases in Resting Muscle Oxygen Consumption after a Women’s Soccer Match - Bonilla, Aldo Alfonso Vasquez; Timon, Rafael; Camacho-Cardeñosa, Alba; Camacho-cardeñosa, Marta; Guerrero, Samantha; Olcina, Guillermo (International Journal of Sports Medicine, 2020)
Currently, near infrared spectroscopy has a clear potential to explain the mechanisms of fatigue by assessing muscle oxygenation. The objective of the study was to observe the changes in muscle oxygen consumption after an official women’s soccer match. The sample was 14 players who competing in the second division of Spain of women’s soccer. They were evaluated before, immediately after and 24 h after the official match. Biochemical parameters were measured in blood plasma (BUN, GOT, LDH, CPK). The jumping in countermovement, perceived exertion and perceived muscle pain were also assessed. The muscle oxygen consumption and muscle oxygen saturation were evaluated in the gastrocnemius muscle with an arterial occlusion test. ANOVA of repeated measures, Pearson’s correlation and Hopkins’ statistics were applied to measure the magnitudes of change and effect size. There was observed an increase in kinetics of SmO2 at 24 h after the official match, using arterial occlusion. In addition, it was found that the increase in muscle oxygenation correlated with fatigue indicators, such as the increases in LDH, perceived muscle pain and the decrease in countermovement. It is confirmed that a women’s soccer match produced an increase of resting muscle oxygenation in 24 h after the official match.
Keywords: fatigue; muscle oxygen saturation; nirs; women’s soccer; training